Intracellular galectins control cellular responses commensurate with cell surface carbohydrate composition. (25th September 2019) - Hong, Ming-Hsiang; Lin, Wei-Han; Weng, I-Chun; Hung, Yu-Hsien; Chen, Hung-Lin; Chen, Huan-Yuan; Chen, Peilin; Lin, Chun-Hung; Yang, Wei Yuan; Liu, Fu-Tong
Abstract: Galectins are β-galactoside-binding animal lectins primarily found in the cytosol, while their carbohydrate ligands are mainly distributed in the extracellular space. Cytosolic galectins are anticipated to accumulate on damaged endocytic vesicles through binding to glycans initially displayed on the cell surface and subsequently located in the lumen of the vesicles, and this can be followed by cellular responses. To facilitate elucidation of the mechanism underlying this process, we adopted a model system involving induction of endocytic vesicle damage with light that targets the endocytosed amphiphilic photosensitizer disulfonated aluminum phthalocyanine. We demonstrate that the levels of galectins around damaged endosomes are dependent on the composition of carbohydrates recognized by the proteins. By super resolution imaging, galectin-3 and galectin-8 aggregates were found to be distributed in distinct microcompartments. Importantly, galectin accumulation is significantly affected when cell surface glycans are altered. Furthermore, accumulated galectins can direct autophagy adaptor proteins toward damaged endocytic vesicles, which are also significantly affected following alteration of cell surface glycans. We conclude that cytosolic galectins control cellular responses reflect dynamic modifications of cell surface glycans.